Britain’s position on the role of France in the issue of the Iskenderun Sanjak between 1918 – 1939 - Alaa Eddin, Ibrahim; Aql, Mirna Khalil (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The British discussed the fate of the Iskenderun brigade in the post-Ottoman state during Hussein McMahon’s correspondence, demonstrating the strategic importance of this territory in British colonial policies of control and influence from the Mediterranean to India. With Turkey, which was strategically evolving to wrest the brigade from Syria (the northern border of the Arab countries) and annex it to Turkey, thus achieving two goals, removing the brigade from French control as Britain’s traditional rival, and ensuring Turkey’s alliance with it in World War II was looming. Although France bears responsibility for the abdication of the Iskenderun Brigade, Britain has played a crucial role in resolving the issue for Turkey. بحثت بريطانية مصير لواء اسكندرون في مرحلة ما بعد الدولة العثمانية خلال مراسلات حسين ماكماهون مما يدل على الأهمية الاستراتيجية لهذا الإقليم في سياسات بريطانية الاستعمارية للسيطرة والنفوذ من البحر المتوسط وحتى الهند, لكن لواء اسكندرون خضع للاستعمار الفرنسي بموجب اتفاقية سايكس بيكو, فسعت بريطانية في إطار علاقاتها مع تركيا التي كانت تتطور على نحو استراتيجي إلى انتزاع اللواء من سوريا (الحدود الشمالية للبلاد العربية) وضمه إلى تركيا, لتحقق بذلك هدفين, إخراج اللواء من السيطرة الفرنسية باعتبارها المنافس التقليدي لبريطانيا, وضمان تحالف تركيا معها في الحرب العالمية الثانية التي كانت تلوح في الأفق. وعلى الرغم من أن فرنسا تتحمل مسؤولية التنازل عن لواء اسكندرون, إلا أن بريطانيا لعبت دوراً حاسماً في حل القضية لصالح تركيا.